Coherent emission from surface Josephson plasmons in striped cuprates - Nicoletti, D; Buzzi, M; Fechner, M; Dolgirev, PE; Michael, MH; Curtis, JB; Demler, E; Gu, GD; Cavalleri, A (National Academy of Sciences, 2022)
The interplay between charge order and superconductivity remains one of the central themes of research in quantum materials. In the case of cuprates, the coupling between striped charge fluctuations and local electromagnetic fields is especially important, as it affects transport properties, coherence, and dimensionality of superconducting correlations. Here, we study the emission of coherent terahertz radiation in single-layer cuprates of the La2-xBaxCuO4 family, for which this effect is expected to be forbidden by symmetry. We find that emission vanishes for compounds in which the stripes are quasi-static but is activated when c-axis inversion symmetry is broken by incommensurate or fluctuating charge stripes, such as in La1.905Ba0.095CuO4 and in La1.845Ba0.155CuO4. In this case, terahertz radiation is emitted by surface Josephson plasmons, which are generally dark modes, but couple to free space electromagnetic radiation because of the stripe modulation.